Piloting an information and communication technology tool to help addressing the challenge of antimicrobial resistance in low-income countries - Mutua, Florence K.; Onono, J.O.; Boqvist, S.; Koech, Patricia; Abdi, Abdullahi M.; Karimi, Hildah; Sternberg-Lewerin, S. (MDPI, 2025)
Background/Objectives: Antimicrobial use (AMU) in livestock drives antimicrobial resistance (AMR). AMR has a significant impact on public health. While several interventions have been used to address this challenge, few have utilized Information and Communication Technology (ICT) approaches. The objective of this study was to pilot and assess an ICT system to monitor the use of veterinary drugs and disseminate information to farmers in peri-urban smallholder poultry systems in Kenya.